Synthesis of Sensor Attacks for Tampering Detectability of Partially Observed Discrete-Event Systems - Chen, Qinrui; Su, Rong; Li, Zhiwu (IEEE transactions on automatic control, 2025)
This paper addresses the problem of the detectability of partially observed discrete-event systems subject to covert sensor attacks. We assume that an attacker can arbitrarily alter sensor readings after intercepting them from a target system, aiming to trick a predefined supervisor to issue improper control commands, making the system not strongly or weakly detectable. The definitions of attackable strong detectability and attackable weak detectability are presented. Necessary and sufficient conditions for the two types of attackable detectability are then derived based on the observer construction. The attack against strong detectability (AASD) problem and attack against weak detectability (AAWD) problem are formulated. It is shown that the supremal (or least restrictive) AASD and AAWD exist and can be computed, as long as the plant model and the supervisor model are regular, i.e., both are representable by finite-state automata.